Outside Front Cover: Plasma Process. Polym. 2/2023. Issue 2 (6th February 2023) - Wang, Huichao; Zhao, Tong; Wang, Zichen; Wang, Xiaolong; Wang, Daohan; Zhang, Yuantao
Abstract : Outside Front Cover : Under the electric field effect of plasma, the cancer cell membrane was deformed to form water bridge across the cell membrane, and eventually led to the formation of perforation. Increasing the electric field intensity, decreasing the frequency speed up this process, and the reduction of cholesterol in cancer cells is the key to the selectivity of plasma. The formation of electroporation helps to kill cancer cells in plasma‐assisted treatment. Further details can be found in the article by Huichao Wang, Tong Zhao, Zichen Wang, Xiaolong Wang, Daohan Wang, and Yuantao Zhang (e2200159 )